Analysis of the CO2 reduction effect of partial utilization of the Additive Manufacturing method to the machining parts production. - Yoshihiro NORIKANE; Hidekazu NISHIMURA (Nihon Kikai Gakkai ronbunshu)
The manufacturing industry has been required to suppress CO2 emissions with the collaboration of the whole supply chain including parts manufacturing. Additive Manufacturing is a novel method that allows flexible production with a minimal amount of material, and the cooperative manufacturing of conventional manufacturing methods and Additive Manufacturing has a potential to suppress CO2 emission in the manufacturing supply chain. In this study, we propose a method to analyze the trade-off between CO2 emissions and parts manufacturing costs in a cooperative manufacturing system between additive manufacturing and conventional manufacturing, using multi-objective optimization method, use cases of parts manufacturing are investigated. A set of conditions that minimize CO2 emissions under a given cost condition is derived as a Pareto set. Sensitivity analysis is conducted to evaluate the impact of factors such as the amounts of materials consumed during parts manufacturing and energy consumption during manufacturing on the reduction of CO2 emissions. Case study is conducted and we derived the optimal condition set. Furthermore, we analyze factors that are sensitive to reduction of CO2 emissions.